How can SMEs signal their quality and growth orientation to the market? An analysis of the cost of Italian corporate mini‐bonds. (28th March 2022) - Boccaletti, Simone; Rossi, Emanuele; Rossolini, Monica
Abstract: We examine how small and medium‐sized enterprises (SMEs) may signal their quality and growth orientation to the market and the effect on the cost of bond funding, which is often high for unlisted firms and SMEs mainly because of their information opacity and higher riskiness. The paper contributes to the growing European debate on market innovations aimed at facilitating funding for smaller and nonlisted firms, breaking from the prior main focus on the cost for large and listed companies of accessing liquid bond markets. We analyze 220 mini‐bonds listed in Italy between 2013 and 2017 to examine determinants of yield spreads. Our explanatory variables are size, age, and tangible assets—all indicators of the firm's information opacity—together with the issuer's growth opportunities, rating availability, and the presence of a guarantee. The findings suggest that tangible assets can ease the asymmetric information and associated monitoring costs for investors, thus reducing the bond yield spread. More significantly, the yield spread depends on the type of investment project financed: risky growth projects are associated with a higher cost of funding than other types of projects. Under such circumstances, the rating represents an informative instrument for the market in assessing issuers' growth orientation.